2012
DOI: 10.1039/c2dt30080j
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric aluminum–phosphorus compounds as masked frustrated Lewis pairs for small molecule activation

Abstract: Hydroalumination of aryldialkynylphosphines RP(C≡C-(t)Bu)(2) (R = Ph, Mes) with equimolar quantities of diethylaluminum hydride afforded mixed alkenyl-alkynyl cyclic dimers in which the dative aluminum-phosphorus bonds are geminal to the exocyclic alkenyl groups. Addition of triethylaluminum to isolated 1 (R = Ph) or to the in situ generated species (R = Mes) caused diethylaluminum ethynide elimination to yield the arylethylphosphorus dimers 2 and 3. These possess a chair-like Al(2)C(2)P(2) heterocycle with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 80 publications
7
79
0
4
Order By: Relevance
“…[183] Efforts to make analogous geminal P/B FLP (C 6 F 5 ) 2 BCH 2 P t Bu 2 were unsuccessful as this species effects ortho-C À F activation affording the heterocycle (C 6 F 5 )C 6 F 4 BFCH 2 P t Bu 2 (451; Scheme 126). [170] Analogous hydroaluminations [102] of RP(CC t Bu) 2 with Et 2 AlH (R = Ph, Mes) afford dimeric, six-membered rings resulting from a Al-P donor-acceptor interaction ( (456). Despite the dimeric nature, these species bind CO 2 or PhNCO affording products containing five-membered rings 457-459.…”
Section: Bu 3 Ph][mentioning
confidence: 99%
“…[183] Efforts to make analogous geminal P/B FLP (C 6 F 5 ) 2 BCH 2 P t Bu 2 were unsuccessful as this species effects ortho-C À F activation affording the heterocycle (C 6 F 5 )C 6 F 4 BFCH 2 P t Bu 2 (451; Scheme 126). [170] Analogous hydroaluminations [102] of RP(CC t Bu) 2 with Et 2 AlH (R = Ph, Mes) afford dimeric, six-membered rings resulting from a Al-P donor-acceptor interaction ( (456). Despite the dimeric nature, these species bind CO 2 or PhNCO affording products containing five-membered rings 457-459.…”
Section: Bu 3 Ph][mentioning
confidence: 99%
“…compound 1, Scheme 1), are synthesized on a facile route by hydroalumination of sterically shielded dimesitylalkynylphosphines. [3] Less bulky substituents led to the formation of dimeric compounds by intermolecular Al-P interactions, [5,15] or adducts were isolated, in which the starting alkynes or dialkylaluminum hydrides were coordinated by the aluminum and phosphorus atoms of an intermediately formed FLP. [16] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[2] An advantage of these aluminum compounds is the inherently high Lewis acidity of aluminum atoms, which do not need an activation by electron withdrawing fluorinated substituents. The outstanding properties of these FLPs allowed the activation or complexation of various substrates such as carbon dioxide, [3][4][5] terminal alkynes, [3,6] alkenes, [7] hydrogen, [8] carbonyl compounds, [9] isocyanates, [5] hydrogen halides, [10] or transition metal complexes. [11] Their specific acceptor and donor capability was used for the unprecedented solubilization of alkali metal hydrides in hydride transfer reactions [12] and phase-transfer catal-of the C=O groups to the Lewis acidic aluminum and the Lewis basic phosphorus atoms (4 to 6).…”
Section: Introductionmentioning
confidence: 99%
“…Uhl and coworkers [62] have also shown that hydroalumination of dialkynylphosphine occurs to form heterocycles which bear dative P-Al bonds. Despite this dative interaction, these bonds are labile and can activate small molecules including CO 2 and isocyanates [62].…”
mentioning
confidence: 95%
“…Despite this dative interaction, these bonds are labile and can activate small molecules including CO 2 and isocyanates [62]. In an unprecedented result, they reported the hydroalumination of an ynamine to give a N/Al FLP system [63].…”
mentioning
confidence: 97%